Pneumatospinning Biomimetic Scaffolds for Meniscus Tissue Engineering - Dorthé, Erik W.; Williams, Austin B.; Grogan, Shawn P.; D’Lima, Darryl D. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanofibrous scaffolds fabricated via electrospinning have been proposed for meniscus tissue regeneration. However, the electrospinning process is slow, and can only generate scaffolds of limited thickness with densely packed fibers, which limits cell distribution within the scaffold. In this study, we explored whether pneumatospinning could produce thicker collagen type I fibrous scaffolds with higher porosity, that can support cell infiltration and neo-fibrocartilage tissue formation for meniscus tissue engineering. We pneumatospun scaffolds with solutions of collagen type I with thicknesses of approximately 1mm in 2 hours. Scanning electron microscopy revealed a mix of fiber sizes with diameters ranging from 1µm to 30µm. The collagen scaffold porosity was approximately 48% with pores ranging from 7.4µm to 100.7µm. The elastic modulus of glutaraldehyde crosslinked collagen scaffolds was approximately 45 MPa, when dry, which reduced after hydration to 0.1 MPa. Mesenchymal stem cells obtained from the infrapatellar fat pad were seeded in the scaffold with high viability (>70%). Scaffolds seeded with adipose-derived stem cells and cultured for three weeks exhibited a fibrocartilage meniscus-like phenotype (expressing COL1A1, COL2A1 and COMP). Ex vivo implantation in healthy bovine and arthritic human meniscal explants resulted in the development of fibrocartilage-like neotissues that integrated with the host tissue with deposition of glycosaminoglycans and collagens type I and II. Our proof-of-concept study indicates that pneumatospinning is a promising approach to produce thicker biomimetic scaffolds more efficiently that electrospinning, and with a porosity that supports cell growth and neo-tissue formation using a clinically relevant cell source.